2021
DOI: 10.1186/s41155-021-00190-z
|View full text |Cite
|
Sign up to set email alerts
|

Factorial validity and measurement invariance of the Psychosocial Uncertainty Scale

Abstract: This study presents the development of the Psychosocial Uncertainty Scale (PS-US), which articulates the perception of uncertainty in the social context and its psychological experience. It was validated with a sample of 1596 students and active professionals (employed and unemployed). By randomly dividing this sample in three sub-samples, the following analyses were performed: exploratory factor analysis (sample one: N = 827); preliminary confirmatory factor analysis identifying the final version of the scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…After testing the factorial and measurement validity of all scales as previously mentioned, a Structural Equation Model (SEM) was performed to test if financial access has effects on psychosocial uncertainty and emotional uncertainty (expecting it to protect against it), personal agency and SPC (potentially increasing both), and on SDO; if dimensions of psychosocial uncertainty have effects on emotional coping, personal agency, SPC, and SDO, expecting psychosocial uncertainty to have greater effects than emotional coping and personal agency, possibly undermining SPC and having effects on greater levels of SDO (while personal agency could have the inverse effect), if SPC has a negative effect on SDO, and to explore which of these variables may act as mediators in this model. The definition of each effect tested was based on the literature review and previous results on the relationship between financial access, psychosocial uncertainty, and emotional coping ( Lucas Casanova, 2021 ; Lucas Casanova et al, 2021 ), adding direct effects of financial access on SPCS and SDO (as suggested by the literature review). Regarding the relationship between psychosocial uncertainty, SPC and SDO, preliminary models were tested for psychosocial uncertainty and SPC, and psychosocial uncertainty and SDO.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After testing the factorial and measurement validity of all scales as previously mentioned, a Structural Equation Model (SEM) was performed to test if financial access has effects on psychosocial uncertainty and emotional uncertainty (expecting it to protect against it), personal agency and SPC (potentially increasing both), and on SDO; if dimensions of psychosocial uncertainty have effects on emotional coping, personal agency, SPC, and SDO, expecting psychosocial uncertainty to have greater effects than emotional coping and personal agency, possibly undermining SPC and having effects on greater levels of SDO (while personal agency could have the inverse effect), if SPC has a negative effect on SDO, and to explore which of these variables may act as mediators in this model. The definition of each effect tested was based on the literature review and previous results on the relationship between financial access, psychosocial uncertainty, and emotional coping ( Lucas Casanova, 2021 ; Lucas Casanova et al, 2021 ), adding direct effects of financial access on SPCS and SDO (as suggested by the literature review). Regarding the relationship between psychosocial uncertainty, SPC and SDO, preliminary models were tested for psychosocial uncertainty and SPC, and psychosocial uncertainty and SDO.…”
Section: Resultsmentioning
confidence: 99%
“…The URS and PS-US were also previously validated for Portuguese ( Lucas Casanova et al, 2019b , 2021 ). Here, only the dimension emotional coping of the URS will be used since it proved to be the one that had more explanatory power for issues concerned with socioeconomic circumstances and its relationship with the dimensions of the PS-US in previous studies ( Lucas Casanova et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations